Optimization of heat transfer in a solid torus: A parametric and numerical approach under natural convection - Kumud Ranjan; Gloria Biswal; Sachindra Kumar Rout; Ahmed Kadhim Hussein; Aboulbaba Eladeb; Badr M. Alshammari; Lioua Kolsi (Case Studies in Thermal Engineering)
In the present work, a horizontally oriented 2D toroidal loop subjected to natural convection and surface radiation is studied numerically. The wall temperature of the torus and the adjacent air is considered to be 450 K and 300 K respectively. Influence of the Rayleigh number (103 to 107) for the laminar region, Aspect ratio (2.5–7.5) and emissivity (0–1) were the parameters considered to examine the thermal characteristics of heat transfer. Ansys Fluent software was used obtain the computational results. The outcome of this investigation affirms that with the increment in the Rayleigh numbers and emissivity, overall Nusselt number upsurges. An effort has also been made to optimize the process parameter through Taguchi model. The response of the process parameters is described by the overall Nusselt number. It has been found the surface emissivity is the most influencing parameter which effects the overall heat transfer followed by Rayleigh number and Aspect ratio.